Dignity and Predictors of Its Change Among Inpatients in Long-Term Care - Kisvetrová, Helena; Tomanová, Jitka; Hanáčková, Romana; Greaves, Peta Jane; Steven, Alison (Clinical nursing research, 2022)
The purpose of this study was to identify any differences in the dignity evaluation of geriatric inpatients after 1 month of hospitalization in a long-term care wards (LTC) and predictors of this change. This follow-up study included 125 geriatric inpatients who filled the Patient Dignity Inventory (PDI-CZ), Geriatric Depression Scale, Barthel Index, and Mini-Mental State Examination. In the initial measurement, the patients rated of PDI-CZ item "Not able to perform tasks of daily living" the worst. One month after, the items "Not able to perform tasks of daily living," "Not able to attend to bodily functions," and "Not feeling worthwhile or valued" were improved. Patients with higher education, for whom self-sufficiency improved and depression decreased, rated their dignity more positively 1 month after the hospitalization in LTC. Our findings suggest that these factors are important for the maintenance of the dignity of older adults hospitalized in LTC.
Keywords: Inpatients; Long-Term Care; Respect; následné studie; hospitalizace; uznání; education; self-sufficiency; dlouhodobá péče; Aged; dignity; long-term care; senioři; geriatric patient; Follow-Up Studies; hospitalizovaní pacienti; lidé; Humans; Hospitalization; depression